AIDS PREVENTION AND HEALTH AMONG STUDENTS IN THE 21 ST OF CENTURE - Shukurova Sevara (Academia Science Repository, 2023)
This article provides information about AIDS and HIV infection, ways of transmission, disease prevention, and recommendations for promoting a healthy lifestyle among young people.